REDAKSI DAN DAFTAR ISI - Februari 2018, Mimbar Keadilan (Mimbar Keadilan, 2018)
Pemimpin RedaksiWiwik Afifah, S.Pi., S.H., M.H. Sekretaris RedaksiTomy Michael, S.H., M.H. Dewan PenyuntingDr. Krisnadi Nasution, S.H., M.H.Dr. Endang Prasetyawati, S.H., M.H.Dr. Sri Setiadji, S.H., M.H.Dr. Erny Herlin Setyorini, S.H., M.H. Penyunting BahasaMuh. Jufri Ahmad, S.H., M.H., M.M. Mitra BebestariProf. Dr. Mashudi, S.H., M.H.Prof. Dr. Teguh Prasetyo, S.H., M.Si.Prof. Dr. I Dewa Gede Atmaja, S.H.Prof. Dr. Tjuk Wirawan, S.H.Prof. Dr. IB. Supancana, S.H., M.H.Prof. Dr. Zudan Arif F, S.H., M.H.Prof. Dr. I Nyoman Nurjaya, S.H., M.H.Dr. Harjono, S.H., M.C.L. Pelaksana AdministrasiKasdi, S.Sos.